Importância da vegetação ripária em região intensamente desmatada no sudeste do Brasil: um estudo com peixes de riacho - Teresa, Fabricio Barreto; Casatti, Lilian (My University, 2010)
e investigated whether the presence of degraded riparian forests along streams influences the fish communities' composition in comparison with environments completely deforested. Stream stretches (1st to 3rd order) with degraded riparian forest (n = 20) and without riparian forest (n = 20) in the micro-basins of Aguape and Tiete (downstream portion) rivers, northwest of São Paulo, Brazil, were selected for ichthyofauna sampling. Overall, 6,695 individuals, representing six orders, 17 families and 55 species were registered. Forested streams presented higher observed and estimated richness than deforested streams. However, forested streams, on average, had lower total richness and richness of tolerant species than deforested streams, indicating higher beta diversity among forested streams. A difference on the species composition between streams groups was also registered. Most of the unique species to deforested streams, and of those caught in greater abundance and frequency in these streams, are tolerant to structural degradation of the habitat. In contrast, most species that occurred exclusively or preferentially in forested streams have specialized habits and are more dependent on micro-habitats associated with the presence of riparian vegetation. Our results indicate that streams with riparian vegetation, though degraded, are able to maintain distinct communities when compared to those found in completely deforested streams, allowing the occurrence of species with more specialized habits and contributing to the maintenance of communities regionally more diverse.
The importance of riparian forest in intensely deforested region in southeastern Brazil: a study with stream fish.